Rural community perceptions and preferences toward loan sharks: A case study in Padang Pariaman Regency from an Islamic finance perspective - Erizal Candra Efendi; Muchlis Bahar; Duhriah; Salmy Edawati Yaacob; Irwandi Jaswir (Indonesian Journal of Islamic Economics Research, 2026)
This study examines rural community perceptions of loan shark practices, the factors driving dependence on informal lending, and the potential of sharia-based financing alternatives in Padang Pariaman Regency. Using a qualitative descriptive field approach, data were collected through in-depth interviews, participant observation, and documentation across five sub-districts. The findings indicate that loan sharks are perceived as fast, simple, and accessible sources of financing for urgent household and micro-business needs. However, their high interest rates and rigid installment systems are considered burdensome and exploitative. Although most respondents recognize that such practices involve riba and contradict Islamic principles, borrowing persists due to unstable income, limited savings, and restricted access to formal and Islamic financial institutions. Community reliance is therefore driven more by structural constraints than by acceptance of interest-based transactions. This study highlights the need to strengthen accessible, fast, and inclusive Islamic microfinance as a viable alternative to reduce dependence on loan sharks.